Predlog nove klasifikacije kožnih limfomov - Chimenti, Sergio (Radiology and oncology (Ljubljana), 1999)
The currently used classifications of cutaneous lymphomas, such as that of Kiel, are based on their histologic characteristic, not distinguishing betweenprimary and secondary cutaneous lymphomas. Therefore, their practical value is limited. The new classification combines clinical, histologic, immunohistochemical and genetic criteria which instruct the treatment of the individual patient. Lymphomas are divided into T and B-cell types, and to the respect of their evolution and prognosis the indolent, intermediate, agressiveand provisory group are defined.
Keywords: Classification; Lymphoma; Lymphoma, B-cell; Lymphoma, T-cell; Skin neoplasms